The Dependence of Water Permeability in Quartz Sand on Gas Hydrate Saturation in the Pore Space. Issue 2 (15th February 2018) - Kossel, E.; Deusner, C.; Bigalke, N.; Haeckel, M.
Abstract: Transport of fluids in gas hydrate bearing sediments is largely defined by the reduction of the permeability due to gas hydrate crystals in the pore space. Although the exact knowledge of the permeability behavior as a function of gas hydrate saturation is of crucial importance, state‐of‐the‐art simulation codes for gas production scenarios use theoretically derived permeability equations that are hardly backed by experimental data. The reason for the insufficient validation of the model equations is the difficulty to create gas hydrate bearing sediments that have undergone formation mechanisms equivalent to the natural process and that have well‐defined gas hydrate saturations. We formed methane hydrates in quartz sand from a methane‐saturated aqueous solution and used magnetic resonance imaging to obtain time‐resolved, three‐dimensional maps of the gas hydrate saturation distribution. These maps were fed into 3‐D finite element method simulations of the water flow. In our simulations, we tested the five most well‐known permeability equations. All of the suitable permeability equations include the term (1‐ S H ) n, where S H is the gas hydrate saturation and n is a parameter that needs to be constrained. The most basic equation describing the permeability behavior of water flow through gas hydrate bearing sand is k = k 0 (1‐ S H ) n . In our experiments, n was determined to be 11.4 (±0.3). Results from this study can be directly applied to bulk flow analysis under the assumption of homogeneous gas hydrate saturation and can be further used to derive effective permeability models for heterogeneous gas hydrate distributions at different scales. Key Points: Flow behavior and gas hydrate saturation during CH4 hydrate formation in sand were monitored Different permeability equations were tested for ability to reproduce experimental results Equations of form k (1‐ S H ) n show best agreement with data